Pengaruh Financial Distress dan Return On Assets (ROA) terhadap Tax Avoidance (Studi Empiris pada Perusahaan yang Terdaftar di Indeks IDX 30 Bursa Efek Indonesia Tahun 2019-2022) - Larasati, Lovieta Perdani Arryfah; Afifudin, Afifudin; Nandiroh, Umi (Universitas Islam Malang, 2024)
This research aims to determine and analyze the extent of the influence of financial distress as measured using the Altman Z-Score and return on assets as measured using ROA on tax avoidance as measured using Effective Tax Rate (ETR) in companies listed on the IDX 30 index of the Indonesia Stock Exchange for 2019-2022. This research is quantitative research. This research sample was obtained using a purposive sampling method, where there were only 48 companies that met all the criteria. The analytical method used is multiple regression analysis with the help of SPSS tools to test the influence of each variable on tax avoidance. The result of this research found that financial distress and return on assets have no effect on tax avoidance.Keywords : Financial distress, return on assets, tax avoidance